Family Social Norms and Child Labor - Gil Epstein (Centre for Research & Analysis of Migration (CReAM), Department of Economics, University College London, 2021)
Child labor is a widespread phenomenon and therefore is of interest to both researchers and policy makers. Various reasons for the existence of child labor have been proposed with the goal of designing appropriate solutions. While household poverty is viewed as the main reason for child labor, we choose to focus on the phenomenon that parents who worked during own childhood are more likely to send their children to work. We also look at the effect of social norms on the parents' child labor decision and analyze both these effects on the supply of labor and equilibrium in the labor market. Finally, we suggest an explanation for the phenomenon of poor societies with similar income levels that differ significantly in literacy rates and propose policy improvements.
Keywords: D13; D64; D91; J22; Z10; 330; Child Labor; Social norms; Intergenerational Transmission